Pengaruh Brand Luxury dan Brand Awareness terhadap Willingness To Pay (Studi pada Konsumen Pembeli Motor dengan Mesin diatas 500cc di Indonesia) - Danny Marcheta Alfitrada (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Motorcycle industry competition in Indonesia continues toincrease in any class: entry, middle, or high level. Brandhas its typical characteristic, and this particularitydistinguishes one product from another, albeit of thesame type. Motor sport is a type of motorcycle that lookslike a motor racing or has a performance above the averagemotorcycle type of duck or scooter. Motor sport is a type ofmotor that has more performance and control. Drivingposition was focused to maintain the point of gravity sothat control is more controlled. This study used a sampleof 150 respondents taken from the population of motorvehicle owners with engine capacities over 500cc. Samplingusing accidental sampling method. Characteristics of respondents selected by gender, age, employment status,and education level. Instrument test used to test theinstrument of this study in the form of validity and reliabilitytest. Hypothesis test using t test. Data analysis techniques use multiple linear regression. In the classical assumptiontest, the multicollinearity free regression model, noheteroscedasticity, and normal distribution. The resultof subsequent analysis shows that the variable of luxurybrand and brand awareness used in this research havea positive effect on willingness to pay on consumer ofmotorcycle buyer with machine capacity above 500cc in Indonesia. Keywords: Brand Luxury, Brand Awareness, Willingness to Pay